Expanding Horizons: A Pilot Mentoring Program Linking College/Graduate Students and Teens With ASD. (February 2016) - Curtin, Carol; Humphrey, Kristin; Vronsky, Kaela; Mattern, Kathryn; Nicastro, Susan; Perrin, Ellen C.
A small pilot program of 9 youth 13 to 18 years old with high-functioning autism spectrum disorder (ASD) or Asperger's syndrome assessed the feasibility, acceptability, and potential efficacy of an individualized mentoring program. Youth met weekly for 6 months with trained young adult mentors at a local boys and girls club. Participants reported improvements in self-esteem, social anxiety, and quality of life. Participants, parents, mentors, and staff reported that the program improved participants' social connectedness. Although the pilot study was small, it provides preliminary data that mentoring for youth with ASD has promise for increasing self-esteem, social skills, and quality of life.